THE ANALYSIS OF THE LIPETSK PHARMACEUTICAL MARKET OF NASAL GLUCOCORTICOSTEROID - K. V. Danilova; I. M. Razdorskaya (Фармакоэкономика, 2015)
in the present paper we have studied a group of pharmaceutical drugs used in the treatment of a widely spread today medical condition – allergic rhinitis. We have developed a conceptual approach to the analysis of the local market, which allowed us to elicit the main trends and peculiarities of the pharmaceutical market of nasal glucocorticosteroids of Lipetsk. As a result of research we identified the leaders of sales on the market nasal glucocorticosteroid, Lipetsk: drugs Nasobek market share – 31.1%, Nasonex with a market share of 26.4%, Awami and Flixonase – 20.4% and 14.8%, respectively.